2016
DOI: 10.1038/eye.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors of scleral rupture due to blunt ocular trauma

Abstract: PurposeTo describe and identify ocular and wound characteristics, and prognostic factors associated with final visual acuity (VA) in patients with scleral rupture due to blunt ocular trauma.MethodsThe medical records of 61 patients with globe rupture due to blunt ocular trauma who underwent primary repair were reviewed retrospectively. The data recorded included demographic characteristics, initial and final VA, ocular signs, wound characteristics, and surgeries. Initial VA, ocular signs, wound characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
6
17
0
3
Order By: Relevance
“…In eyes with scleral rupture limited to zone II and zone III, Yucel et al observed that as high as 42.6% of eyes resulted in final vision of NPL. Poor final VA was significantly associated with poor presenting VA, horizontal midline wound, longer wound length, presence of hyphema, vitreous hemorrhage or retinal detachment, and no cataract surgery 29 . In this study, approximately one-fourth (26%) of eyes had NPL.…”
Section: Discussionmentioning
confidence: 95%
“…In eyes with scleral rupture limited to zone II and zone III, Yucel et al observed that as high as 42.6% of eyes resulted in final vision of NPL. Poor final VA was significantly associated with poor presenting VA, horizontal midline wound, longer wound length, presence of hyphema, vitreous hemorrhage or retinal detachment, and no cataract surgery 29 . In this study, approximately one-fourth (26%) of eyes had NPL.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the distinct features of ocular injuries, children with penetrating injuries tend to experience a more obvious deterioration in visual acuity 16 , making it easier for parents to notice the penetrating injury and take the child to the hospital at that time. However, the onset of traumatic cataract due to blunt injury tends to be gradual, which might delay proper treatment and result in an unsatisfactory prognosis in many children 20 . In children who mention being hit in the eye, regardless of whether there is immediate vision loss or wounds around the eyeball, parents should closely observe the child’s eye for timely detection of injuries requiring surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Severe trauma is one of the main causes of evisceration [11, 12]. Analysis of the aforementioned factors may help to develop targeted prevention procedures to reduce the frequency of resorting to this devastating ocular treatment option.…”
Section: Introductionmentioning
confidence: 99%